2006
DOI: 10.1111/j.1742-7843.2006.pto_455.x
|View full text |Cite
|
Sign up to set email alerts
|

A Metabonomics Study of the Hepatotoxicants Galactosamine, Methylene Dianiline and Clofibrate in Rats*

Abstract: Abstract:The efficacy of high-resolution 1 H nuclear magnetic resonance ( 1 H-NMR) spectroscopy-based metabonomics was studied in a model of rat liver toxicity. Hepatotoxicities were induced in male rats using methylene dianiline, clofibrate and galactosamine. Twenty-four-hr urine from days 1 to 5 after treatment were subjected to 1 H-NMR evaluation of the biochemical effects. Blood were also taken at Days 2, 3 and 5 to examine biochemical changes associated with hepatotoxicities, and histopathological changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…A prominent finding was the depletion of the TCA cycle intermediates which were mainly located in liver mitochondria, including citrate, succinate, and 2-oxoglutarate, in urine samples from the combined group. These organic acids may be more universal markers for cellular liver pathology (Ishihara et al, 2006). The decreased levels of citrate, 2-oxoglutarate, and succinate in urine following PCBs and TCDD treatment could be a result of decreased fatty acid catabolism, since these metabolites are intermediates of the TCA cycle which occurs largely in liver mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…A prominent finding was the depletion of the TCA cycle intermediates which were mainly located in liver mitochondria, including citrate, succinate, and 2-oxoglutarate, in urine samples from the combined group. These organic acids may be more universal markers for cellular liver pathology (Ishihara et al, 2006). The decreased levels of citrate, 2-oxoglutarate, and succinate in urine following PCBs and TCDD treatment could be a result of decreased fatty acid catabolism, since these metabolites are intermediates of the TCA cycle which occurs largely in liver mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis has been introduced into toxicological research to obtain better understanding of the endogenous metabolic profile in several hepatic injury models over the last decade (Soga et al, 2006;Ishihara et al, 2006). One advantage of this evolving technology is to assess a number of endogenous metabolites in blood or urine at one time.…”
Section: Introductionmentioning
confidence: 99%
“…To identify putative metabolites associated with cholestasis, urine samples obtained were subjected to 1 H nuclear magnetic resonance analysis. Previous studies using various types of hepatotoxicants (4,4¢-methylene dianiline, clofibrate and galactosamine) suggested that urinary metabolites with chemical shifts of 0.66 to 1.90 ppm were markedly affected by 4,4¢-methylene dianiline [12], which is known to induce cholestasis. The dose of 4,4¢-methylene dianiline, 250 mg/kg, oral administration, in one previous study was relatively high and might have injured tissues other than the liver [27].…”
Section: Discussionmentioning
confidence: 99%
“…peroxisome proliferation in the liver and hepatocyte death, respectively [12]. The most significant differences between the 4,4¢-methylene dianiline-treated groups (250 mg/kg oral administration) and groups treated with other agents (clofibrate 500 mg/kg oral administration, galactosamine 500 mg/kg intraperitoneal administration) were observed in chemical shifts of peaks mainly between 0.66 and 1.90 ppm.…”
mentioning
confidence: 92%
See 1 more Smart Citation